Comparison of Commercial Arbitration: The United States & Latin America - (:unkn) unknown (My University, 2016)
It has been said that the United States and Latin America have historically taken different attitudes toward arbitration. The document will proceed with a general description of arbitration in Latin America and conclude with a focus on Brazil, Venezuela, and Mexico. ... It furthers this goal by allowing a party to petition a federal district court to compel arbitration, to appoint an arbitrator if one has not been designated, and to enforce an award.